Enhanced Recovery after an Innovative Percutaneous Endoscopic Transforaminal Lumbar Interbody Fusion for the Treatment of Lumbar Spinal Stenosis: A Prospective Observational Study. (20th December 2021) - Yin, Peng; Gao, Haifeng; Zhou, Lijin; Pang, Daming; Hai, Yong; Yang, Jincai
Abstract : Background . The objective of this study was to investigate the enhanced recovery clinical effects of an innovative percutaneous endoscopic transforaminal lumbar interbody fusion (PE-TLIF) for the treatment of patients with LSS and degenerative instability. Methods . From January 2019 to March 2020, 51 patients with single-segment LSS and degenerative instability were prospectively included in our study (ChiCTR1900020679). The Oswestry Disability Index (ODI), the visual analogue scale (VAS) on lumbar and leg pain (VAS-LBP and VAS-LP), serum creatine kinase (CK), the peak intensity of sulphur hexafluoride microbubble contrast agent (PI), and the maximal cross-sectional area of multifidus muscle (Max-CSA) around the surgical incision were assessed preoperatively, postoperatively, and at regular follow-up. Results . All patients were followed up. The mean postoperative bedridden time was 20.45 ± 2.66 hours. The ODI, VAS-LBP, and VAS-LP were improved significantly after operation compared to these data before operation in all the patients (P < 0.05 ). The CK at 1 day after operation was higher compared to the data before the operation (P < 0.05 ), and there was no significant difference on CK at 1 week after operation (P > 0.05 ). The PI at 1 week after operation was higher compared to this item before operation (P < 0.05 ), and there was no significant difference on PI at 1 month or 3 months after operation (P > 0.05 ). The Max-CSA at 1 week after operation was higher compared to this item before the operation (P < 0.05 ), and there was no significant difference in Max-CSA at 1 month or 3 months after operation compared with before the operation (P > 0.05 ). Conclusions . Our results and systematic review presented the innovative PE-TLIF technique could obtain satisfactory and effective outcomes for the treatment of patients with LSS and degenerative instability. Our PE-TLIF technique also had the ability to decrease the MF injury and obtain an enhanced recovery.